Double cross-linked carboxymethyl chitosan-based hydrogel and its preparation method and application

The bicroscroscarmellosan-based hydrogel prepared by chemical-physical dual crosslinking technology, loaded with silver nanoparticles, solved the problem of adhesion after absorbing moisture by existing wound dressings, and significantly improved antibacterial performance, achieving effective support for wound healing.

CN114773625BActive Publication Date: 2025-04-15OCEAN UNIV OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210344426.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-02
Publication Date
2025-04-15
Estimated Expiration
2042-04-02

AI Technical Summary

Technical Problem

Existing wound dressings may excessively adhere to wounds and new tissues when absorbing moisture, resulting in pain and secondary damage. At the same time, insufficient antibacterial performance can easily lead to bacterial infection.

Method used

By chemically-physical bicroscroslinking carboxymethyl chitosan with silane and calcium ions, a bicrosslinked carboxymethyl chitosan-based hydrogel was prepared and loaded with silver nanoparticles, giving the hydrogel antibacterial and anti-inflammatory properties.

Benefits of technology

The hydrogel has good mechanical properties and cell compatibility, can effectively inhibit bacterial infection, ensure the stable release of silver nanoparticles, and maintain good antibacterial activity within 16 days.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114773625B_ABST
    Figure CN114773625B_ABST
Patent Text Reader

Abstract

The invention discloses a double cross-linked carboxymethyl chitosan-based hydrogel, which is a chemical-physical double cross-linked hydrogel made of carboxymethyl chitosan, a silane cross-linking agent and calcium ions as raw materials, and its preparation method is: at room temperature, a silane cross-linking agent, 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride and a soluble calcium salt are added to a carboxymethyl chitosan solution, mixed, and allowed to stand until no flow phenomenon occurs, and a double cross-linked carboxymethyl chitosan-based hydrogel is obtained. The application of the double cross-linked carboxymethyl chitosan-based hydrogel in the preparation of a medical dressing that promotes wound healing. The double cross-linked carboxymethyl chitosan-based hydrogel of the present invention has good mechanical properties, good cell compatibility, toughness and deformability, and does not need to add synthetic polymer materials and initiators during preparation; after loading silver nanoparticles, it has a good antibacterial effect, can ensure that the silver nanoparticles are stably released within 16 days, and can effectively inhibit bacterial infection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a double-crosslinked carboxymethyl chitosan-based hydrogel and a preparation method and application thereof, and belongs to the field of biomaterials and natural polymer materials. Background Art

[0002] After skin injury, a large amount of fluid will be lost from the wound, and infection may occur, causing severe tissue necrosis. Therefore, wound care is extremely important. The development of wound dressings aims to protect the healing wound from the invasion of the external environment and to help the wound healing process itself. Initially, gauze or cotton dressings were used, which can quickly absorb blood and form a barrier between the wound and the outside world. However, during the use of cotton gauze, it may absorb water excessively and adhere to the wound and new tissue, causing pain and secondary damage when it is removed. When changing the dressing, it may also be invaded by external bacteria and cause the wound to become infected. With the development of medicine, the concept of "moist wound environment" is conducive to skin wound repair has been widely studied and recognized, thus proposing an ideal biological wound dressing. Because the structure of hydrogel is similar to the natural extracellular matrix, it can meet the needs of biological wound dressings. At the same time, various drugs or growth factors can be incorporated to give hydrogels more properties to accelerate wound healing. Based on these properties, hydrogels are considered to be one of the promising biological wound dressing materials.

[0003] Chitosan is a type of product produced by the deacetylation of chitin in nature. As a natural polysaccharide, it has multiple properties such as non-toxicity and biocompatibility. Natural polysaccharide-based hydrogels usually have poor mechanical properties. In order to ensure that the dressing has appropriate mechanical properties, synthetic polymers are often introduced to maintain the integrity of the dressing. However, in this process, there may be problems such as excessive initiators or inability to remove them.

[0004] Bacterial infection causes the inflammatory response to persist and hinders the normal repair of wounds, which seriously threatens human health. Antibiotics have long been used to prevent and treat bacterial infections, but the extensive and excessive use of antibiotics will increase bacterial antibiotic resistance. Silver nanoparticles have attracted attention because of their low toxicity, broad-spectrum antibacterial activity and ability to meet the needs of low drug resistance, but they tend to aggregate due to the presence of dipole-dipole attraction, resulting in weakened or even lost antibacterial activity. Therefore, it is necessary to develop suitable natural polysaccharide-based antibacterial dressings loaded with silver nanoparticles to alleviate these problems. Summary of the invention

[0005] In view of the above-mentioned prior art, the present invention provides a double cross-linked carboxymethyl chitosan-based hydrogel and an antibacterial hydrogel. The present invention obtains a natural polysaccharide-based hydrogel carrier with good mechanical properties by chemically and physically cross-linking carboxymethyl chitosan with silane and calcium ions, and can also load silver nanoparticles, thereby giving the hydrogel antibacterial and anti-inflammatory properties.

[0006] The present invention is achieved through the following technical solutions:

[0007] A double cross-linked carboxymethyl chitosan-based hydrogel is a chemical-physical double cross-linked hydrogel made from carboxymethyl chitosan, a silane cross-linking agent and calcium ions as raw materials, and is prepared by the following method: at room temperature, a silane cross-linking agent, 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride (DMT-MM) and a soluble calcium salt are added to a carboxymethyl chitosan solution, mixed evenly, and allowed to stand until no flow occurs, thereby obtaining a double cross-linked carboxymethyl chitosan-based hydrogel.

[0008] A double cross-linked carboxymethyl chitosan-based antibacterial hydrogel is composed of the double cross-linked carboxymethyl chitosan-based hydrogel and silver nanoparticles loaded thereon, and can be prepared by the following method: at room temperature, silver nanoparticles, a silane cross-linking agent, 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride (DMT-MM) and a soluble calcium salt are added to a carboxymethyl chitosan aqueous solution, mixed evenly, and allowed to stand until no flow occurs, thereby obtaining the double cross-linked carboxymethyl chitosan-based antibacterial hydrogel.

[0009] Furthermore, the silane crosslinking agent is selected from 3-aminopropyltriethoxysilane (APTES).

[0010] Furthermore, the soluble calcium salt is selected from calcium chloride.

[0011] Furthermore, the amount of the carboxymethyl chitosan and the silane crosslinking agent is in the following relationship: 1 mmol of the silane crosslinking agent is added to every 7-8 grams of carboxymethyl chitosan, preferably 1 mmol of the silane crosslinking agent is added to every 7.4 grams of carboxymethyl chitosan.

[0012] Furthermore, the molar ratio of the 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride (DMT-MM) to the silane crosslinking agent is 1.0 to 1.5:1, preferably 1.25:1.

[0013] Furthermore, the molar ratio of the silane crosslinking agent to calcium ions is 1.2 to 1.8:1, preferably 1.5:1.

[0014] Furthermore, the amount of the silver nanoparticles added is: 60-65 mg of silver nanoparticles per 1 gram of carboxymethyl chitosan, preferably 62.5 mg.

[0015] Furthermore, the concentration of the carboxymethyl chitosan solution is 4% (mass to volume ratio, unit: g / ml), and the solvent is 0.1% acetic acid solution (mass to volume ratio, unit: g / ml).

[0016] Furthermore, the silane crosslinker, 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride and soluble calcium salt are all added in the form of a solution; the solvent of the solution is a MES buffer solution (MES buffer solution is a commercial product in the prior art).

[0017] Furthermore, the silver nanoparticles are added in the form of a solution; the solvent of the solution is a MES buffer solution.

[0018] Specifically, the preparation method of the double-crosslinked carboxymethyl chitosan-based hydrogel is as follows: at room temperature, 75 µL of DMT-MM solution, 75 µL of APTES solution and 75 µL of CaCl2 solution are added to 1.5 ml of a 4% carboxymethyl chitosan aqueous solution, mixed, and allowed to stand until no flow occurs, thereby obtaining a double-crosslinked carboxymethyl chitosan-based hydrogel; the solvents of the DMT-MM solution, the APTES solution and the CaCl2 solution are all MES buffer solutions, the concentration of the DMT-MM solution is 0.136 mol / L; the concentration of the APTES solution is 0.108 mol / L; and the concentration of the CaCl2 solution is 0.072 mol / L.

[0019] Specifically, the preparation method of the double-crosslinked carboxymethyl chitosan-based antibacterial hydrogel is as follows: at room temperature, 75µL of AgNPs solution, 75µL of DMT-MM solution, 75µL of APTES solution and 75µL of CaCl2 solution are added to 1.5 ml of 4% carboxymethyl chitosan aqueous solution, mixed, and allowed to stand until no flow occurs, thereby obtaining a double-crosslinked carboxymethyl chitosan-based hydrogel; the solvents of the AgNPs solution, DMT-MM solution, APTES solution and CaCl2 solution are all MES buffer solutions; the concentration of the AgNPs solution is 50 mg / ml; the concentration of the DMT-MM solution is 0.136 mol / L; the concentration of the APTES solution is 0.108 mol / L; and the concentration of the CaCl2 solution is 0.072 mol / L.

[0020] Application of the double-crosslinked carboxymethyl chitosan-based hydrogel in preparing a medical dressing for promoting wound healing.

[0021] Application of the double-crosslinked carboxymethyl chitosan-based antibacterial hydrogel in preparing a medical dressing for promoting wound healing.

[0022] The double cross-linked carboxymethyl chitosan-based hydrogel of the present invention is a chemical-physical double cross-linked hydrogel made of carboxymethyl chitosan, a silane cross-linking agent and calcium ions as raw materials, has good mechanical properties, good cell compatibility, toughness and deformability, and does not need to add synthetic polymer materials and initiators during preparation. The double cross-linked carboxymethyl chitosan-based hydrogel of the present invention can be loaded with silver nanoparticles to prepare a double cross-linked carboxymethyl chitosan-based antibacterial hydrogel, which has good antibacterial effect, can ensure the stable release of silver nanoparticles within 16 days, can be used as a wound healing medical dressing, and can effectively inhibit bacterial infection.

[0023] Various terms and phrases used herein have the general meanings that are well known to those skilled in the art. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 : Diagram of the gelation state of carboxymethyl chitosan-based hydrogel.

[0025] Figure 2 : Synthesis mechanism diagram of double-cross-linked carboxymethyl chitosan-based antibacterial hydrogel dressing.

[0026] Figure 3 : Mechanical properties curve of carboxymethyl chitosan-based hydrogel.

[0027] Figure 4 : Release curve of silver ions from double-cross-linked carboxymethyl chitosan-based antibacterial hydrogel dressing.

[0028] Figure 5 : Anti-Escherichia coli and Staphylococcus aureus effects of double-cross-linked carboxymethyl chitosan-based hydrogels without and with silver nanoparticles.

[0029] Figure 6 : Figure 5 Statistical graph of the number of colonies on the agar plate.

[0030] Figure 7 : In vitro cytotoxicity effect of double-cross-linked carboxymethyl chitosan-based hydrogel.

[0031] Figure 8 :Diagram of the wound repair process in mice.

[0032] Fig. 9 : Schematic diagram of the changes in the proportion of unclosed wound area in mice.

[0033] Fig.10 : H&E staining histomorphological examination of mouse wound surface.

[0034] Fig.11 : Biodegradation curve of double-cross-linked carboxymethyl chitosan-based antibacterial hydrogel dressing. DETAILED DESCRIPTION

[0035] The present invention will be further described below in conjunction with the embodiments. However, the scope of the present invention is not limited to the following embodiments. It will be appreciated by those skilled in the art that various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention.

[0036] The instruments, reagents, materials, etc. involved in the following embodiments, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following embodiments, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art.

[0037] All data results of the present invention are expressed as mean ± standard deviation. The statistical significance was measured by one-way analysis of variance (ANOVA). * P<0.05, ** P<0.01 was considered a statistically significant difference.

[0038] Example 1 Preparation of carboxymethyl chitosan / silane single cross-linked hydrogel

[0039] (1) Weigh 3.6 g of carboxymethyl chitosan (CMC) and place it in 90 mL of 0.1% acetic acid solution. Stir and dissolve it at room temperature until the system becomes a transparent liquid. Let it stand at room temperature to defoam, and a CMC solution with a concentration of 4% (w / v) is obtained.

[0040] (2) Weigh 0.096 g of 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride (DMT-MM) and dissolve it in 3 mL of the prepared MES buffer solution to form a DMT-MM solution (0.136 M). Pipette 96 µL of 3-aminopropyltriethoxysilane (APTES) and dissolve it in 2.04 mL of the MES buffer solution to form an APTES solution (0.108 M).

[0041] (3) Preparation of hydrogel by inverted bottle method: Take 1.5 mL CMC solution, add 75 µL DMT-MM solution and 75 µL APTES solution, stir evenly, and let stand at room temperature until no flow occurs. Then, carboxymethyl chitosan / silane single cross-linked hydrogel (CMCs-APTES) is prepared. The gelation state of the hydrogel is shown in the figure below. Figure 1 As shown, Figure 1 The bottle on the far left is a carboxymethyl chitosan solution without the addition of a cross-linking agent. Although the carboxymethyl chitosan solution at this concentration is viscous, it does not form a gel.

[0042] Example 2 Preparation of carboxymethyl chitosan / silane / calcium ion double cross-linked hydrogel

[0043] (1) Weigh 0.128 g of calcium chloride and place it in 4 mL of MES buffer solution to dissolve it into a CaCl2 solution (0.072 M).

[0044] (2) Preparation of hydrogel by inverted bottle method: 1.5 mL of 4% (w / v) CMC solution prepared in Example 1 was taken, and 75 μL of CaCl2 solution, 75 μL of DMT-MM solution (prepared in Example 1) and 75 μL of APTES solution (prepared in Example 1) were added thereto in sequence. The mixed solution was quickly stirred and allowed to stand at room temperature until no flow phenomenon occurred. Thus, carboxymethyl chitosan / silane / calcium ion double cross-linked hydrogel (CMCs-APTES-Ca) was prepared. The gelation state of the hydrogel is shown in the figure below. Figure 1 shown.

[0045] Example 3 Preparation of carboxymethyl chitosan / silane / calcium ion double cross-linked hydrogel dressing

[0046] (1) Weigh 25 mg of silver nanoparticles into 500 µL of MES buffer solution and disperse them by ultrasonication to obtain AgNPs solution.

[0047] (2) Take 1.5 mL of the CMC solution prepared in Example 1, add 75 µL of the AgNPs solution, and stir slowly until uniform to obtain a mixed solution.

[0048] (3) The hydrogel dressing was prepared by the inverted bottle method: 75 μL of DMT-MM solution (prepared in Example 1), 75 μL of APTES solution (prepared in Example 1) and 75 μL of CaCl2 solution (prepared in Example 2) were added to the above mixed solution in sequence, and the mixed solution was quickly stirred. The mixed solution was quickly stirred evenly and allowed to stand at room temperature until the flow phenomenon no longer occurred. Thus, a carboxymethyl chitosan / silane / calcium ion double cross-linked hydrogel dressing (CMCs-APTES-Ca-AgNPs) was prepared. The gelation state of the hydrogel is shown in the figure below. Figure 1 The synthesis mechanism diagram of the hydrogel dressing is shown in Figure 2 Silane acts as a covalent cross-linker and acts as a covalent bond between polymers. The carboxyl groups on carboxymethyl chitosan complex with calcium ions to form a double cross-linked network. Silver nanoparticles are introduced into the system to obtain CMCs-APTES-Ca-AgNPs hydrogel dressing.

[0049] Example 4 Testing of the tensile properties of hydrogels

[0050] The tensile performance test method of the hydrogel is as follows: a 4.8 cm × 2.5 cm rectangular hydrogel is prepared according to the methods of Example 1, Example 2 and Example 3, the surface moisture is removed, the stretching speed is set to 20 mm / min, the initial stretching length is 5 mm, the thickness is 0.75 mm, and the stretching test is performed on a universal testing machine and repeated three times. The results are as follows Figure 3 As shown in the figure, the tensile stress of the double-crosslinked carboxymethyl chitosan-based hydrogel CMCs-APTES-Ca can reach 46.87±2.50 KPa, which is higher than that of the single-crosslinked carboxymethyl chitosan-based hydrogel CMCs-APTES, and the degree of deformation is also enhanced, and the toughness is improved. After adding loaded AgNPs, it still maintains a good stress state and can withstand more external forces.

[0051] Example 5 In vitro silver ion release test of hydrogel dressing

[0052] The in vitro silver ion release detection method of the hydrogel dressing is as follows: 200 µL of CMC solution is taken, and CMCs-APTES-Ca-AgNPs hydrogel is prepared according to the ratio of Example 3. The hydrogel is placed in 50 mL centrifuge tubes containing 25 mL of 10mM PB solution of pH=6.0 and pH=8.0, respectively, and placed in a 37°C constant temperature oscillator for 16 days. On the 1st, 2nd, 4th, 8th, 12th, and 16th days of release, 1.5 mL of solution is taken from each centrifuge tube and placed in a 2 mL EP tube, and 1.5 mL of PB solution of the corresponding pH value is added to each centrifuge tube in time. The solutions obtained on different days are diluted and passed through a membrane, and the released silver ion content is determined by an inductively coupled plasma mass spectrometer (ICP-MS). The results are as follows: Figure 4 As shown, Ag + It can be continuously released from the CMCs-APTES-Ca-AgNPs hydrogel network and can be released slowly for a long time. On the 16th day, the accumulated silver in the solution at pH = 6.0 and pH = 8.0 was approximately 0.032 mg / L and 0.019 mg / L, respectively (the total content was 0.5 mg / mL, and the release amounts were 0.064‰ and 0.038‰, respectively).

[0053] Example 6 In vitro antibacterial performance test of hydrogel dressing

[0054] The in vitro antibacterial property test method of the hydrogel dressing is as follows: the hydrogels prepared in Example 2 and Example 3 are freeze-dried and placed in 1×10 6 CFU / mL of Escherichia coli ( E. coli ) suspension, 1×10 6 CFU / mL of Staphylococcus aureus ( S. aureus) suspension (the volume of each suspension is 2 ml), incubated in a 37°C constant temperature incubator for 1.5 h, then 100 μL of diluted bacterial solution (suspension diluted 100 times) was evenly applied to the surface of LB solid culture medium, incubated in a 37°C constant temperature incubator for 12 h and the number of colonies was counted. The results are as follows: Figure 5 , Figure 6 As shown. Figure 5 It can be seen that bacteria can still be observed on the agar plate of the bacterial solution treated with CMCs-APTES-Ca hydrogel, but almost no bacteria can be seen on the agar plate coated with the bacterial solution treated with CMCs-APTES-Ca-AgNPs hydrogel. The statistical results of the number of colonies further confirmed the antibacterial properties of CMCs-APTES-Ca-AgNPs hydrogel ( Figure 6 ), its S. aureus and E. coli The mortality rate can reach almost 100%.

[0055] Example 7 In vitro cytotoxicity test of hydrogel dressing

[0056] Prepare hydrogel samples, namely: CMCs-APTES-Ca hydrogel prepared in Example 2, and CMCs-APTES-Ca-AgNPs hydrogel prepared in Example 3. Disinfect the prepared samples with medical alcohol and rinse with sterile phosphate buffered saline (PBS); completely immerse the hydrogel samples in centrifuge tubes containing DMEM serum-free medium with 0.1% double antibody, wherein the mass (g) of the hydrogel material and the volume (mL) of the DMEM serum-free medium are in a ratio of 1:5, and place the centrifuge tubes in a constant temperature oscillator for oscillation, setting the temperature to 37°C and the speed to 100 rpm; on the 1st, 3rd, and 5th days, take out 2 mL of the test solution from the centrifuge tubes, and add 2 mL of DMEM serum-free medium containing 0.1% double antibody to the centrifuge tubes; add 125 µL of fetal bovine serum to the 2 mL of the test solution taken out, and use a needle filter (0.22 µm) to filter through the membrane to obtain the hydrogel extracts on the 1st, 3rd, and 5th days.

[0057] 100 μL of cells were added at a density of 5×10 4 L929 fibroblasts at a concentration of 100 μL / mL were seeded in a 96-well plate, and the temperature of the incubator was set at 37°C and the CO2 concentration was 5%. The cells were cultured in the incubator for 12 hours. After 12 hours, the cell suspension was removed and 100 μL of the hydrogel extracts from the 1st, 3rd, and 5th days were added to each well. The cells were placed in the incubator and cultured for another 12 hours. The cytotoxicity of the hydrogel was evaluated by the CCK-8 method. The control group was cells that were not treated with the hydrogel extracts. The results are shown in Figure 2. Figure 7As shown, the cell survival rates after treatment with hydrogel extracts for different days were all above 90%, and the extracts of CMCs-APTES-Ca hydrogel and CMCs-APTES-Ca-AgNPs hydrogel did not show significant cytotoxic effects on cells.

[0058] Example 8 In vivo healing experiment of hydrogel dressing

[0059] The in vivo safety experiment of antibacterial hydrogel dressing was conducted using 6-week-old male Kunming mice with a body weight of 18-22 g. They were pre-fed for 7 days and kept at room temperature of 20-25°C, humidity of 40%-70%, ventilation frequency of 10-20 times / hour, and 12-h alternating light and dark conditions.

[0060] The wound infection modeling method was as follows: the mice were anesthetized with chloral hydrate (7 wt%, 0.05 mL / 10 g), and the hair on the back of the mice was deeply removed by electric and hair removal cream. A circular skin wound was made on the back of the mice using a skin biopsy opening device with a D=5 mm diameter, and the wound was infected with Staphylococcus aureus (1×10 6 CFU / mL) were used to establish infection models for all wounds.

[0061] The treatment method is as follows: the mice were randomly divided into three groups, namely, the control group (no hydrogel was placed), the CMCs-APTES-Ca hydrogel group (the hydrogel prepared in Example 2), and the CMCs-APTES-Ca-AgNPs hydrogel group (the hydrogel dressing prepared in Example 3). The dressing was changed every 2 days, and the wound was photographed with a digital camera on the 2nd, 6th and 14th day to observe the degree of wound healing. The results are as follows Figure 8 The results are shown in Table 1 and expressed as a percentage of the area of ​​the wound infection model. Fig. 9 . As can be seen from the figure, on the second day, the wounds of each group were infected by Staphylococcus aureus and caused wound decay. On the sixth day of treatment, the wounds of mice in the control group and the experimental group were closed. The closure of the CMCs-APTES-Ca-AgNPs group was more obvious than that of the CMCs-APTES-Ca group and the control group. The wound unclosure rate was about 40.45%, while the wound unclosure rates of the CMCs-APTES-Ca group and the control group were about 74.52% and 69.27%, respectively. On the 14th day of treatment, the proportion of unclosed wound area in the CMCs-APTES-Ca-AgNPs group was reduced to only about 6.37%, while the unclosed wound areas of the CMCs-APTES-Ca group and the control group were about 28.24% and 15.76%, respectively. It can be seen that the CMCs-APTES-Ca-AgNPs hydrogel group had the best wound healing effect among the three treatment methods.

[0062] The histomorphological analysis method of wound healing in mice was as follows: skin tissues from the wounds on the back of mice on the 6th and 14th days were fixed with 10% formalin fixative and embedded in paraffin, and H&E staining histomorphological detection was performed using the standard detection method. Fig.10 As shown, it can be observed that the inflammatory phenomenon in the CMCs-APTES-Ca-AgNPs hydrogel group was weakened compared with the CMCs-APTES-Ca hydrogel group and the Control group. This is related to the silver ions released by the loaded AgNPs. Silver ions can inhibit the growth of Staphylococcus aureus, thereby weakening and accelerating the infiltration of inflammatory cells. On the 14th day, inflammation was no longer observed in the CMCs-APTES-Ca-AgNPs hydrogel group, and there was still a small amount of inflammation in the CMCs-APTES-Ca hydrogel group and the Control group.

[0063] Example 9 Biodegradability test of double cross-linked carboxymethyl chitosan-based hydrogel dressing

[0064] The biodegradability test method is as follows: freeze-dry the hydrogel dressing prepared in Example 3 and record its mass m i , and then buried in the soil. The hydrogel was weighed and the mass m was recorded every seven days. n , the biodegradation rate of the double-crosslinked carboxymethyl chitosan-based hydrogel dressing was calculated and expressed as the residual weight rate (Degradation of residual), as shown in Formula 1. The results are shown in Fig.11 shown.

[0065] Degradation of residual (%) = (m i -m n ) / m i × 100 (Formula 1).

[0066] Fig.11 It shows that after one week of degradation in a natural environment, the residual weight rate of CMCs-APTES-Ca-AgNPs dry hydrogel is about 91.46%. During the overall degradation process, it shows a trend of continuous degradation. At the same time, within the five-week degradation time, the residual weight rate is about 77.34%, and the mass reduction rate is about 22.66%.

[0067] The above examples are provided to those skilled in the art to fully disclose and describe how to make and use the claimed embodiments, and are not intended to limit the scope of the disclosure herein. Modifications that are obvious to those skilled in the art will fall within the scope of the appended claims.

Claims

1. A method for preparing a double cross-linked carboxymethyl chitosan-based hydrogel, characterized in that: At room temperature, silver nanoparticles, a silane crosslinking agent, 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride and a soluble calcium salt are added to a carboxymethyl chitosan aqueous solution, mixed evenly, and allowed to stand until no flow occurs, thereby obtaining a double-crosslinked carboxymethyl chitosan-based antibacterial hydrogel; The silane crosslinking agent is 3-aminopropyltriethoxysilane.

2. The method for preparing a double cross-linked carboxymethyl chitosan-based hydrogel according to claim 1, characterized in that: The soluble calcium salt is selected from calcium chloride.

3. The method for preparing a double cross-linked carboxymethyl chitosan-based hydrogel according to claim 1, characterized in that: The dosage of the carboxymethyl chitosan and the silane crosslinking agent is as follows: 1 mmol of the silane crosslinking agent is added to every 7 to 8 grams of carboxymethyl chitosan; The molar ratio of the 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride to the silane crosslinking agent is 1.0 to 1.5:1; The molar ratio of the silane crosslinking agent to calcium ions is 1.2 to 1.8:

1.

4. The method for preparing a double cross-linked carboxymethyl chitosan-based hydrogel according to claim 1, characterized in that: The concentration of the carboxymethyl chitosan solution is 4%, and the solvent is 0.1% acetic acid solution; The silane crosslinking agent, 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride and soluble calcium salt are all added in the form of a solution; the solvent of the solution is a MES buffer solution.

5. The method for preparing a double cross-linked carboxymethyl chitosan-based hydrogel according to claim 1, characterized in that: The amount of silver nanoparticles added is: 60-65 mg of silver nanoparticles per 1 gram of carboxymethyl chitosan; The silver nanoparticles are added in the form of a solution; the solvent of the solution is a MES buffer solution.

6. The method for preparing a double cross-linked carboxymethyl chitosan-based hydrogel according to any one of claims 1 to 5, characterized in that: At room temperature, 75 µL of AgNPs solution, 75 µL of DMT-MM solution, 75 µL of APTES solution and 75 µL of CaCl2 solution were added to 1.5 ml of 4% carboxymethyl chitosan aqueous solution, mixed and allowed to stand until no flow occurred, thereby obtaining a double-crosslinked carboxymethyl chitosan-based hydrogel; the solvents of the AgNPs solution, DMT-MM solution, APTES solution and CaCl2 solution were all MES buffer solutions; the concentration of the AgNPs solution was 50 mg / ml; the concentration of the DMT-MM solution was 0.136 mol / L; the concentration of the APTES solution was 0.108 mol / L; and the concentration of the CaCl2 solution was 0.072 mol / L.

7. Double cross-linked carboxymethyl chitosan-based hydrogel prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the double-crosslinked carboxymethyl chitosan-based hydrogel according to claim 7 in preparing a medical dressing for promoting wound healing.

Citation Information

Patent Citations

  • Preparation method of bacteriostatic and wound restoration promoting chitosan hydrogel dressing

    CN107496976A

  • Hyaluronic acid derivative modified with poly(ethylene glycol)

    WO2019098393A1